The Mitochondrial PHB Complex Determines Lipid Composition and Interacts With the Endoplasmic Reticulum to Regulate Ageing - Lourenço, Artur B.; Rodríguez-Palero, María Jesús; Doherty, Mary K.; Cabrerizo Granados, David; Hernando-Rodríguez, Blanca; Salas, Joaquín J.; Venegas-Calerón, Mónica; Whitfield, Phillip D.; Artal-Sanz, Marta (Frontiers in Physiology, 2021)
Metabolic disorders are frequently associated with physiological changes that occur during ageing. The mitochondrial prohibitin complex (PHB) is an evolutionary conserved context-dependent modulator of longevity, which has been linked to alterations in lipid metabolism but which biochemical function remains elusive. In this work we aimed at elucidating the molecular mechanism by which depletion of mitochondrial PHB shortens the lifespan of wild type animals while it extends that of insulin signalling receptor (daf-2) mutants. A liquid chromatography coupled with mass spectrometry approach was used to characterise the worm lipidome of wild type and insulin deficient animals upon PHB depletion. Towards a mechanistic interpretation of the insights coming from this analysis, we used a combination of biochemical, microscopic and lifespan analyses. We show that PHB depletion perturbed glycerophospholipids and glycerolipids pools differently in short- versus long-lived animals. Interestingly, PHB depletion in otherwise wild type animals induced the endoplasmic reticulum (ER) unfolded protein response (UPR), which was mitigated in daf-2 mutants. Moreover, depletion of DNJ-21, which functionally interacts with PHB in mitochondria, mimicked the effect of PHB deficiency on the UPRER and on the lifespan of wild type and insulin signalling deficient mutants. Our work shows that PHB differentially modulates lipid metabolism depending on the worm’s metabolic status and provides evidences for a new link between PHB and ER homeostasis in ageing regulation.